Current Trends in Buffalo Milk Production - Zicarelli, Luigi (Journal of Buffalo Science, 2020)
Between 1961 and 2018 on the total number of dairy ruminants, the percentage of buffaloes and the quantity of milk produced by them had an increasing trend from 3.7% to 5.2% and from 5.4 to 15.7%, respectively; this value on the world total "cow milk + buffalo milk" rose to 18.64%. In the Asian continent, buffaloes’ incidence on the total number of dairy ruminants increased slightly (from 10.2% to 11.7%) while the percentage of cattle fell from 38% to 26.4%. In the same period, the percentage of buffalo milk decreased from 44.6% to 36.9%, while cow milk shares increased from 55.4% to 63%. The percentage of milk produced in Pakistan, India, Nepal (after 2010), and especially in Egypt showed a downward trend. In Italy, the trend has always been increasing. The market price of buffalo milk in developing countries does not compensate for costs which are 15% higher than cow’s milk, if only the cost of feeding is considered, and increases to 40% when the difference in kg of milk equivalent between the two species is about 900 kg per lactation. A reduction of the production gap between the two species is difficult to be achieved because the genetic improvement of dairy cattle is performed in industrialized countries with higher financial support. Therefore, a marketing effort is needed to make well-differentiated buffalo products with specific and well-received sensory properties. In this regard, it should also be noted that δ-valerobetaine, a bioactive molecule beneficial for human health, is present in buffalo milk and meat in higher quantities than in cow’s milk.